The Minimal Residual Disease in Non-Hodgkin's Lymphomas: From the Laboratory to the Clinical Practice - Galimberti, Sara; Genuardi, Elisa; Mazziotta, Francesco; Iovino, Lorenzo; Morabito, Fortunato; Grassi, Susanna; Ciabatti, Elena; Guerrini, Francesca; Petrini, Mario (Frontiers in Oncology, 2019)
Minimal residual disease (MRD) in non Hodgkin’s lymphomas (NHLs) still represents matter of interest and debate: indeed, the new available treatments offer higher rates of complete responses and MRD negativity than in the past, with a positive impact on the long-term survival. Furthermore, the introduction of more sensitive and accurate molecular techniques, such as digital PCR (ddPCR) and the next generation sequencing techniques (NGS), increased the possibility of identifying molecular targets to be followed after therapy (such as rearrangement of immunoglobulins, fusion genes or mutations). This review focused on how molecular biology can help to detect MRD in different types of NHLs and how MRD can change the clinical practice in 2019. In follicular lymphoma (FL), contamination of the grafts and molecular disease persistence after transplantation represent a negative prognostic factors. The combination of Rituximab or Obinutuzumab with Bendamustine seems to be the most effective way to clear MRD in FL patients receiving chemo-immunotherapy (further studies are in progress), and also 90Yttrium-Ibritumomab-Tiuxetan offers a deep clearance of molecular disease. Finally, molecular MRD can further stratify PET-negative cases, with subjects both PET- and MRD-negative presenting the best outcome. In aggressive lymphomas, MRD has a relevant prognostic power and can represent the platform for immunotherapy (such as CAR-T). In diffuse large B-cell lymphoma (DLBCL), the assessment of MRD in the plasma (where cell-free DNA and exosomes circulate) seems to be more predictive than the bone marrow analysis or peripheral blood mononuclear cells. Finally, NGS technologies could be more useful than the classical “patient allele-specific PCR” because they can identify any possible clone emerging during the treatment or follow-up, even if different from that identified at diagnosis, thus predicting relapse. After all, the present available molecular approaches can move MRD from the bench side to the clinical practice.